Comparison of flavoured milk on competitive 2000m rowing performance - Chapman, C. (University of Chichester, 2019)
Purpose: Milk has many proven benefits to aid recovery from sporting performance, with an abundance of literature investigating the effects of CM. Research suggests that CM and SM have a desired CHO-PRO ratio which may aid recovery, hydration and stimulate glycogenesis. The aim of this study was to investigate the comparison of CM and SM on 2000m competitive rowing performance, to evaluate the efficiency of milk flavours over a 24-hour recovery period. Methods: Twelve male undergraduate University students (age; 21 years ± 1 years, mass; 76.6 kg ± 9.5kg, height; 180.9 cm ± 4.5 cm, BMI; 23.6 kg/m2 ± 2.8 kg/m2) participated within this repeated measures cross over design. Participants undertook a 2000m competitive row on an ergometer (Concept 2). After which, 800mls of CM or SM was consumed, once 15 minutes post exercise, then additionally 2 hours after. Physiological variables of HR and RPE were measured after a 24 hour recovery period the same protocol was repeated. Food diaries were obtained post testing to analyse additional CHO/PRO intake. Results: An improved performance (time) was reported after the consumption of both milk supplements (F1, 11 = 15.456, p < 0.05, p = 0.002). There were no significant differences reported within main effects; Condition: (F1, 11 = 0.002, p > 0.05, p = 0.968) and Interaction (F1, 11 = 1.446, p > 0.05, p = 0.254). There were no significant differences reported for physiological variables of peak HR, average HR, peak RPE and median RPE. Conclusion: CM and SM did significantly improve 2000m competitive rowing performance with a significant difference displayed within time and no significant difference reported within physiological variables. It can be concluded CM and SM both improve sporting performance, with CM proving to aid recovery more efficiently in comparison to SM despite them both significantly improving sporting performance.